The role and perception of the civitas in late Roman and Frankish Gaul - Allen, S; Allen, Susan Jane (1990)
The thesis examines the role and perceptions of Gallic civitates from A.D. 340 to 840. Civitates are those urban centres which were distinguished as imperial administrative capitals and, later, as episcopal sees. The thesis addresses a number of general questions, among which the most fundamental is that of which urban functions were essential to the role and ideal of the civitas. Other questions raised include the importance of romanitas to urban-based functions and features, the relationship of the episcopal see to the civitas, and the changes brought about by the establishment of Germanic rule. In order fully to examine the above issues, the thesis has been divided into four chapters each dealing with a specific urban function. Thus, civitates are considered in the light of their administrative, religious, military and economic roles. Within each chapter, attention is given not only to the practical operation of these functions, but also to their importance to the civitas in terms of status and prestige. Further efforts are made to distinguish this type of centre from other settlements. The first chapter, however, deals with the use and application of urban and regional terminology - a study which has demonstrated changing attitudes towards civitates and their dependent territories. The thesis has relied, for the most part, on historical evidence. Archaeological material was omitted, because of the limits of time and because of the necessity to evaluate such evidence in detail and on its own. Despite this limitation, it has been possible to examine aspects of the subject not normally considered by urban historians. For, although there have been studies on civitates, most of these have dealt exclusively with their physical features, or have been restricted to limited geographical areas and/or time periods. In the course of the thesis, it has been shown that the history of civitates closely reflects major events, ideals and developments within society. Thus, within the confines of this thesis, it has been possible to illuminate political, religious and cultural changes throughout the period. It is for this reason that a study of this type is important to the further understanding of an otherwise obscure and often neglected period of history.